Socioeconomic pragmatic variation : speech acts and address forms in context - Staley, Larssyn (Pragmatics & beyond, 2018)
"On a regular basis people encounter unfamiliar uses of pragmatic features, such as offers or requests with differing levels of directness or terms of address showing differing amounts of solidarity or deference. Variational pragmatics is the study of such uses, according to region, gender, age, ethnicity and socioeconomic status, among national and sub-national varieties of pluricentric languages. Despite the wide focus just outlined, this volume provides the first study of pragmatic variation across different social classes, using naturally occurring, interactional data. The discourse analyzed here was collected in over twenty restaurant service encounters spanning three price points. The aim of this study is two-fold: to provide a potential framework for how pragmatic variables and their context can be defined, using the concept of a communicative activity, and to investigate socioeconomic variation in pragmatics by taking offers, thanks responses and address forms as examples. This study contributes, both on a methodological and empirical level, to the growing body of research in variational pragmatics, as well as speech acts, terms of address, relational work and sociolinguistics"--